ANALISIS PENGARUH ATRIBUT CORPORATE GOVERNANCE TERHADAP UNDERPRICING PADA INITIAL PUBLIC OFFERINGS (IPO) DI BURSA EFEK INDONESIA - Isti Nazilah Hidayati; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the influence of corporate governance attributes like non- executive board size, non-executive board independent, non-executive board reputation, ownership concentration, and institutional ownership on the level of underpricing. This study used firm size, profitability, firm age, auditor reputation and underwriter reputation as control variable. The population in this study consists of all IPO firm in Indonesia Stock Exchange for the period 2006-2013. Sampling is done by using purposive sampling method. Total sample of this research is 114 companies that was underpriced on the IPO. This study used multiple regression analysis for hypotheses testing. The result of this study showed that all of the corprate governance atributes which was studied like non executive board size, non-executive board independent, non-executive board reputation, ownership concentration, and institutional ownership not proven significant effects on the level of underpricing.